D-dimer as a Potential Biomarker of Severity in Children Confirmed with COVID-19 - Hanum Ferdian; Rustam Siregar; Annang Giri Moelyo (Molecular and Cellular Biomedical Sciences, 2022)
Background: Coronavirus disease 2019 (COVID-19) in children spreads easily and has a relatively high incidence. Severe complications in children confirmed with COVID-19 are thought to be related to the multisystem inflammatory syndrome, which is associated with coagulation disorders. D-dimer is a fibrin degradation end product which is easy to examine, affordable, fast and reliable. This study investigated the potency of D-dimer levels as a biomarker and assessed optimal cut-off value of D-dimer on severity of COVID-19 in children. Materials and methods: An analytical observational study with a cross-sectional design was conducted in children aged 1-18 years confirmed to have mild, moderate or severe COVID-19 who were treated in the isolation room of Dr. Moewardi Hospital, Surakarta, Indonesia from September 2021 to February 2022. Statistical analysis was conducted using Mann- Whitney test and p<0.05 was considered as statistically significant. The cut-off value of D-dimer was determined with the receiver operating characteristic (ROC) curve. Results: There were 39 children with COVID-19. They were in mild (n=14; 35.9%), moderate (n=19; 48.7%) and severe (n= 6; 15.4%) stages. There were significant differences in D-dimer levels between mild and moderate stages (p=0.001), and mild and severe stages (p=0.001). No significant difference in D-dimer levels between moderate and severe stages (p=0.162). The cut-off value of D-dimer was 485 μg/mL with 92% sensitivity and 71.4% specificity. Conclusion: D-dimer can be used as a potential biomarker of severity in children with COVID-19.Keywords: D-dimer, COVID-19, severity, children